Chemical examination of Polyscias serrata Balf. Family Araliaceae - Anh Tuyet, Nguyen Thi; Phi Phung, Nguyen Kim (Vietnam Journal of Chemistry, 2014)
Amixture 3-O-β-D-glucopyranosylstigmasta-5,22-diene 1aand3-O-β-D-glucopyranosylstigmasta-7,22-diene 1b, 1’-O-benzyl-β-D-glucopyranoside 2 and (8Z)-2-(2-hydroxypentacosanoylamino)octadeca-8-ene-1,3,4-triol 3 were the first time isolated from Polyscias serrata. Among them, compound 3 was the first time found in the genus Polyscias